(untitled) (Comprehensive Journal of Science, 2025)
This research aims to study the current occupational safety and environmental procedures implemented at the oil port of Misurata, and analyze the effectiveness in reducing industrial accidents and oil spills, which are among the main threats to the safety of workers and the surrounding marine environment. The study addressed the main sources of risk within the port, such as oil leaks from pipelines and oil tankers, and the impact of the absence or weak enforcement of safety procedures on increasing the likelihood of these incidents. The research adopted a descriptive-analytical approach, where data was collected through field visits, direct observations, interviews with workers, and analysis of relevant documents and reports. The study concluded that there is a disparity in the implementation of safety procedures between managerial and technical levels, and there is an urgent need to enhance safety culture, update emergency prevention and response systems, and intensify practical training for workers.